Globalization and the Paradigm of Islamic Law Implementation in Aceh - Murdani, Danial (Fakultas Syariah UINSI Samarinda, 2022)
Abstract This paper aims to identify and describe the global challenges that have influenced the Islamic law implementation in Aceh. Further, this article analyses Aceh's Islamic sharia law implementation paradigm based on these global challenges. This article is qualitative research with a descriptive analysis approach. The study found that the challenges of globalization that influenced the Islamic sharia law implementation in Aceh have multi-dimension issues. Those multi-dimension issues are privatization of religion, a decrease in family relationships, demographic revolution, the emergence of an artificial environment, the threat of species extinction and dangers to the climate and tropical forests, the emergence of new moral standards, appearance of innovations such as synthetic food, crime-based technology, knowledge-based education, and other disasters. Based on these global challenges, the Islamic sharia law implementation in Aceh needs a new paradigm. A new paradigm has to be connected with values, problems, and responsive and anticipative methods of Islamic sharia implementation. Implementing Islamic values constitutes the mission of protecting human rights, including protecting religion, life, property, generation, reason, honor, and the environment. Keywords: Globalization, Islamic Sharia, Islamic law implementation in Aceh